Electric bikes and motorized scooters - Popularity and burden of injury. Ten years of National trauma registry experience. (September 2021) - Savitsky, Bella; Radomislensky, Irina; Goldman, Sharon; Kaim, Arielle; Bodas, Moran; ,; Acker, A.; Aviran, N.; Bahouth, H.; Bar, A.; Becker, A.; Braslavsky, A.; et al.
Abstract: Background: Electric bikes (E-bikes) and motorized scooters (M-scooters) have become extremely popular worldwide and in Israel. This change has been followed by an increase in injury-related hospitalizations among these road users. Methods: A retrospective cohort study was performed based on 4733 E-bike or M-scooter riders hospitalized in one of the 19 trauma centers participating in the Israeli National Trauma Registry (INTR) between 2010 and 2020. Results: A persistent increase in the proportion of E-bike/M-scooter riders among hospitalized traffic casualties was observed: from only 0.06% in 2010 to 10.2% in 2020. Although a decrease in the proportion of children riders (<16 years) was observed, their proportion was still high (22% in 2020). Collisions between electric tools (e-tools) and motorized vehicles resulted in 35.6% of the hospitalizations, which were more severe (the proportion of ISS 16+ was 19.2% vs. 11.2%, p < .0001), included severe head injuries (17.2% vs. 11.3%, p < .0001) and a higher mortality rate (1.2% vs. 0.3%, p < .0001) compared to casualties not colliding with a motorized vehicle. The gradual increase in injury severity was observed from 7.8% in 2014 to almost 15% in 2019. Helmet usage among e-tool riders is still inadequate, whereas the lack of helmet use at the time of the accident was higher among children under age 16 (51.0% vs. 39.3%, p < .0001). Conclusions: The findings of this study indicate a worrying trend of an increase in trauma injuries associated with the use of e-tools. As these modes of transportation become more popular and legislative changes have been introduced which have restricted these tools to utilization on roads where the potential of colliding with a motorized vehicle increases, it is expected that the number of injuries will continue to grow. There is need for interventions aimed at increasing awareness for these vulnerable road users targeted at improving riding behaviors and enforcement of helmet usage. Highlights: The development of e-tool specific cycling paths trails behind the growing popularity of these road users. There is a worrying trend of an increase in injuries associated with the use of e-tools. There is an urgent need to improve the safety of these environmentally friendly methods of transportation.